2022
DOI: 10.1042/cs20220450
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid imbalance of cystic fibrosis exists at birth independent of feeding in pig and ferret models

Abstract: Persons with cystic fibrosis (CF) exhibit a unique alteration of fatty acid composition, marked especially among polyunsaturates by relative deficiency of linoleic acid and excess of Mead acid. Relative deficiency of docosahexaenoic acid is variably found. However, the initial development of these abnormalities is not understood. We examined fatty acid composition in young CF ferrets and pigs, finding abnormalities from the day of birth onward including relative deficiency of linoleic acid in both species. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Our results indicate marked abnormalities in lung LCFA uptake by CFTR loss. Previous studies reported altered LCFA levels in people with CF; linoleic acid (C18:2), eicosatrienoic acid (C20:3), docosahexaenoic acid (C22:6), and arachidonic acid (C20:4) are the LCFAs most often cited ( 43 , 65 70 ). However, dietary fat malabsorption due to pancreatic failure and altered intestinal function cloud interpretation in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate marked abnormalities in lung LCFA uptake by CFTR loss. Previous studies reported altered LCFA levels in people with CF; linoleic acid (C18:2), eicosatrienoic acid (C20:3), docosahexaenoic acid (C22:6), and arachidonic acid (C20:4) are the LCFAs most often cited ( 43 , 65 70 ). However, dietary fat malabsorption due to pancreatic failure and altered intestinal function cloud interpretation in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In CF mice, some models also fail to demonstrate a reduction in LA in the serum [ 21 ], while other CF mouse models do exhibit a reduction [ 14 , 22 ]. A recent manuscript identified a reduction in LA in CF pigs and CF ferrets [ 23 ]. This suggests a species-specific and age-specific changes in LA in animal models of CF.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of LA in the diet is ~1.5% [ 24 ], with rats in this study consuming ~3% [ 16 ]. It has been shown in vitro that elevated LA in the culture media increases lung epithelial cell LA concentrations [ 23 , 25 ]; therefore, elevated LA in the diet may increase the concentrations in serum. Notably, the rats in this study were non-fasted, with samples collected in the light cycle, where rodents graze less.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the ileal genetic changes in essential fatty acid metabolic pathways in the rat model (contribution 5), may provide us with a better understanding about the pathological changes associated with CF in non-lung tissue. Interestingly, a study in the CF pig demonstrated that the essential fatty acid changes are not due to diet, as these changes exist at birth [17]. Thus, in addition to changes in cell signal transduction and transport, ion channel dysfunction may lead to imbalances in lipid metabolism.…”
mentioning
confidence: 99%